2021
DOI: 10.1002/gch2.202000076
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Lopsided Blood‐Thinning Drug Increases the Risk of Internal Flow Choking Leading to Shock Wave Generation Causing Asymptomatic Cardiovascular Disease

Abstract: The discovery of Sanal flow choking in the cardiovascular‐system calls for multidisciplinary and global action to develop innovative treatments and to develop new drugs to negate the risk of asymptomatic‐cardiovascular‐diseases. Herein, it is shown that when blood‐pressure‐ratio (BPR) reaches the lower‐critical‐hemorrhage‐index (LCHI) internal‐flow‐choking and shock wave generation can occur in the cardiovascular‐system, with sudden expansion/divergence/vasospasm or bifurcation regions, without prejudice to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(72 citation statements)
references
References 83 publications
2
70
0
Order By: Relevance
“…In a nutshell, we have proved conclusively that the high-BHCR reduces the risk of flow choking as dictated by Eq.1, which is an indisputable physical condition, without any ex vivo or in vivo model support, for prohibiting asymptomatic stroke in any vessel [20][21][22][23]. We concluded that for a healthylife all subjects with high-BPR inevitably have high-BHCR for reducing the risk of the internal flow choking (biofluid/Sanal-flow-choking) triggering the AHF due to the shock wave generation and pressure overshoot (36)(37)(38)(39). We corroborated herein that, the AHF is a transient episode and not an illness.…”
Section: Discussionmentioning
confidence: 94%
“…In a nutshell, we have proved conclusively that the high-BHCR reduces the risk of flow choking as dictated by Eq.1, which is an indisputable physical condition, without any ex vivo or in vivo model support, for prohibiting asymptomatic stroke in any vessel [20][21][22][23]. We concluded that for a healthylife all subjects with high-BPR inevitably have high-BHCR for reducing the risk of the internal flow choking (biofluid/Sanal-flow-choking) triggering the AHF due to the shock wave generation and pressure overshoot (36)(37)(38)(39). We corroborated herein that, the AHF is a transient episode and not an illness.…”
Section: Discussionmentioning
confidence: 94%
“…[1] Such problems of urgency to the scientific communities are the prediction and attenuation of detonation in reacting fluid flow systems and that of asymptomatic stroke (AS) in the human circulatory system (HCS). Note that the deflagration to detonation transition (DDT) in reacting fluid flow systems and the creeping flow to asymptomatic hemorrhagic stroke (AHS) in biological systems could happen due to the consequence of the Sanal flow choking [1][2][3][4][5][6][7][8][9] <https://pubmed.ncbi.nlm.nih.gov/32837737/>. Over the decades several in vitro and in silico studies were reported on DDT in various chemical energy systems from yocto to yotta scales but there were no authentic answers on the fundamental cause of DDT in real-world fluid flow systems.…”
Section: Introductionmentioning
confidence: 99%
“…This physical situation is analogous to the creeping flow to the choked flow condition in an artery with the divergent/bifurcation/vasospasam region causing AHS (see Figure 1(a-h) as the central illustration). 8 Herein, we made an effort to correlate the radical theory of the Sanal flow choking in the human circulatory system (HCS) because blood is a compressible fluid. [1] Furthermore, in vitro study shows (see Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations